Psychometric Properties of the Indonesian Version of Self-Critical Rumination Scale - Eirene Kezia Simarmata; Angelica Augustine Marito; Lusi Nur Ardhiani (Universitas Mercu Buana Jakarta, 2026)
The Self-Critical Rumination Scale (SCRS) measures maladaptive repetitive thinking focused on perceived flaws and failures. Limited research has examined its psychometric properties among engineering students. This study aimed to adapt and evaluate the Indonesian version of the SCRS. Participants were 181 engineering students from Diponegoro University (119 males, 62 females). The scale demonstrated good reliability. Confirmatory factor analysis supported a single-factor structure with acceptable loadings and satisfactory model fit. Convergent validity with the Emotion Reactivity Scale (ERS) showed a strong positive correlation, indicating higher self-critical rumination is associated with greater emotional reactivity. These findings indicate that the Indonesian SCRS is a reliable and valid instrument for assessing self-critical rumination in young adults.